Heavy Metals Concentration in Commercial Rice Available at Erbil City Markets, Iraq and Soaking Effects (Baghdad Science Journal, 2023)
Heavy metal (HM) pollution has long been a significant source of environmental deterioration and a problem for the safety of food. Iraqis prefer rice over any other food, and since heavy metals have a direct impact on health, their traces in rice have drawn particular attention. Before cooking rice, it is usual in Iraq to wash and soak it. Some 55 varieties of imported and local rice were sampled from Erbil city markets in 2022 with the aim of determining the concentration of As, Cd, Cr, Ni and Pb before and after soaking. Standard procedure of acid digestions was applied on the raw and soaked samples. The solutions were analyzed using ICPE-9820 Shimadzu. The mean concentrations of As, Cd, Cr, Ni and Pb (in mg/kg) in the rice samples before soaking was 0.655, 0.170, 0.160, 0.387, 0.489, respectively and after soaking 0.421, 0.109, 0.115, 0.124 and 0.336, respectively. The concentration of As and Pb was found to be beyond the optimum level of 0.2 mg/kg codex standards for rice; whereas Cd and Cr were within the proposed level of codex standards. Moreover, local rice showed higher concentration of (Cd and Cr), whereas (AS and Pb) concentration in imported rice was higher. Further, results validated that rice soaking can decrease levels of As, Cd, Cr, Ni and Pb (32.5%, 40.2%, 27.9%, 61.6% and 31.3%, respectively). These findings suggest that soaking as a kitchen practice has efficiency to evaporate metals and has a great influence on the reduction of toxic heavy metals and thus reduces exposure to toxic metals in rice